Wide, green spaces - Bender, Andrew
Singapore Airlines in-flight magazine salutes five cities around the world that are leading the way in green development: Portland, Oregon, USA; Copenhagen, Denmark; Vancouver, British Columbia, Canada; Curitiba, Brazil; and Singapore.